Clinical and molecular characterization of a multi-institutional cohort of pediatric spinal cord low-grade gliomas. Issue 1 (24th August 2020) - Grob, Sydney T; Nobre, Liana; Campbell, Kristen R; Davies, Kurtis D; Ryall, Scott; Aisner, Dara L; Hoffman, Lindsey; Zahedi, Shadi; Morin, Andrew; Crespo, Michele; Nellan, Anandani; Green, Adam L; et al.
Abstract: Background: The mitogen-activated protein kinases/extracelluar signal-regulated kinases pathway is involved in cell growth and proliferation, and mutations in BRAF have made it an oncogene of interest in pediatric cancer. Previous studies found that BRAF mutations as well as KIAA1549–BRAF fusions are common in intracranial low-grade gliomas (LGGs). Fewer studies have tested for the presence of these genetic changes in spinal LGGs. The aim of this study was to better understand the prevalence of BRAF and other genetic aberrations in spinal LGG. Methods: We retrospectively analyzed 46 spinal gliomas from patients aged 1–25 years from Children's Hospital Colorado (CHCO) and The Hospital for Sick Children (SickKids). CHCO utilized a 67-gene panel that assessed BRAF and additionally screened for other possible genetic abnormalities of interest. At SickKids, BRAF V600E was assessed by droplet digital polymerase chain reaction and immunohistochemistry. BRAF fusions were detected by fluorescence in situ hybridization, reverse transcription polymerase chain reaction, or NanoString platform. Data were correlated with clinical information. Results: Of 31 samples with complete fusion analysis, 13 (42%) harbored KIAA1549–BRAF . All 13 (100%) patients with confirmed KIAA1549–BRAF survived the entirety of the study period (median [interquartile range] follow-up time: 47 months [27–85 months]) and 15 (83.3%) fusion-negative patients survived (follow-up time: 37.5 months [19.8–69.5 months]). Other mutations of interest were also identified in this patient cohort including BRAF V600E, PTPN11, H3F3A, TP53, FGFR1, and CDKN2A deletion. Conclusion: KIAA1549–BRAF was seen in higher frequency than BRAF V600E or other genetic aberrations in pediatric spinal LGGs and experienced lower death rates compared to KIAA1549–BRAF negative patients, although this was not statistically significant.